Lifelong learning : the education of the aging population - Wang, Qiu; Wan, Guofang; Fantacone, Dominick (Chinese American Educational Research and Development Association book series., 2025)
Lifelong Learning: The Education of the Aging Population focuses on the education of the aging population worldwide. The book includes studies representing a variety of perspectives and research methods, rich and informative in analyzing the issue under country-specific social, cultural, historical, economic, and political contexts, and strategies to improve life-long education of aging society. The chapters address Key trends, status, major theories, and models of life-long education for the aging population across a variety of communities Issues and challenges that exist in life-long education for the aging population Effective and successful practices and models that may benefit other countries. The book unites expert researchers, educators, advocates, policymakers, and community leaders from various countries to offer insights, key trends, theories, and practices in education for the aging population, aiming to positively influence lifelong learning for this group globally.